A system for monitoring and reporting outcomes performances of students using Tableau dashboard and PA-ANAS tool for personal/student advisor / Mohaiyedin Idris ... [et al.] - Mohaiyedin Idris (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2016)
Most lecturers in the faculty of Universiti Teknologi MARA (UiTM) are assigned as personal/student advisor (PA). The role of PA in the faculty is to assist students in the scope of personal, social, practical, financial and academic while studying at UiTM. The implementation of Outcome Based Education-Student Centered Learning (OBE-SCL) is imposed by the academic affair in sustaining graduate's qualities. Therefore all assessment activities must be aligned and measured with respect to course outcomes (COs) and program outcomes (POs). In this paper, the capabilities of a continuous student monitoring instrument based on OBE-SCL criteria aligning with PA channel is presented. The instrument is known as PA-ANAS (Personal/Student Advisor-Analysis System) system which is developed by the OBE unit at the Faculty of Electrical Engineering UiTM Pulau Pinang. The system utilizes graphical user interface mechanisms (GUI) together with a database to obtain details of student's POs achievement under the supervision of a PA. Using this system, a PA can always monitor, provide recommendations and ensure that each student will be able to achieve performance index of POs. In order to improve the reporting of a student's POs performances, the concept of storytelling utilizing a Tableau dashboard software which features an interactive and attractive visualization is adopted. The dashboard provides compact information with one click button and meaningful analyses for better and fast decision making in order to enhance POs performances.